A novel mannose-binding lectin from Liparis nervosa with anti-fungal and anti-tumor activities. (27th August 2020) - Jiang, Na; Wang, Yuqing; Zhou, Jing; Zheng, Ruxiao; Yuan, Xiao; Wu, Miaomiao; Bao, Jinku; Wu, Chuanfang
Abstract: Plant lectins are carbohydrate-binding proteins with nonimmune origin, which can reversibly bind with carbohydrates, agglutinate cells, and precipitate polysaccharides and glycoconjugates. Plant lectins have attracted much attention for their anti-virus, anti-proliferation, and pro-apoptosis properties. Thus the exploration of new lectins has received special attention. Here we purified a mannose-binding lectin from the rhizomes of Liparis nervosa by ion exchange chromatography on DEAE-Sepharose, affinity chromatography on Mannose-Sepharose 4B, and gel filtration chromatography on Sephacryl S-100. The purified L. nervosa lectin (LNL) was identified to be a monomeric protein with a molecular mass of 13 kDa. LNL exhibited hemagglutinating activity towards rabbit erythrocytes, and its activity could be strongly inhibited by D-mannose, N-acetyl glucosamine and thyroglobulin. In vitro experiments showed that LNL exhibited a comparable anti-fungal activity against Piricularia oryzae (Cavara), Bipolaris maydis, Fusarium graminearum, and Sclerotium rolfsii, and anti-proliferation activity against tumor cells by inducing apoptosis. The full-length cDNA sequence of LNL is 715 bp in length and contains a 525 bp open reading frame (ORF) encoding a 110-residue mature protein. It was predicted to have three mannose-binding conserved motifs 'QXDXNXVXY'. The binding pattern of LNL was further revealed by homology modeling and molecular docking. We demonstrated that LNL is not only a potential therapeutic candidate against tumor but also a new anti-fungal agent.